2016
DOI: 10.21107/infestasi.v11i2.1133
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH KARAKTERISTIK PEMERINTAH DAERAH DAN TEMUAN AUDIT BPK TERHADAP KINERJA PENYELENGGARAAN PEMERINTAHAN DAERAH (Studi Empiris Pada Pemerintah Kabupaten/Kota Di Provinsi NTB)

Abstract: This study aimed to examined the effect of the characteristics of the local government and BPK audit findings on the performance of the regional administration of the district/city governments in West Nusa Tenggara Province in 2011-2013. Data were collected by using documentation technique and literature. Tests carried out using multiple linear regression test against all regencies/cities in NTB Province which amounted to 10 (ten) Regency/City among others,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 3 publications
4
9
1
4
Order By: Relevance
“…The result of this study supports the statement from Masdiantini & Erawati (2016) which states that the BPK audit findings did not affect the financial performance of the district / city governments in Bali. Artha et al (2015) also supports the results of this study. However, the results of this study are not consistent with (Mangkunegara, 2015).…”
Section: The Effect Of Misstatement To the Financial Performance In Wsupporting
confidence: 91%
See 2 more Smart Citations
“…The result of this study supports the statement from Masdiantini & Erawati (2016) which states that the BPK audit findings did not affect the financial performance of the district / city governments in Bali. Artha et al (2015) also supports the results of this study. However, the results of this study are not consistent with (Mangkunegara, 2015).…”
Section: The Effect Of Misstatement To the Financial Performance In Wsupporting
confidence: 91%
“…Mangkunegara (2015) used one of the elements of the financial statements, namely capital expenditure presented at the LRA, to predict its effect on the financial performance of regional governments in improving the welfare of the community. Mangkunegara (2015) proposed that the variable capital expenditure of regional governments be re-examined because the findings were not consistent with the research conducted byMarfiana & Kurniasih (2013).Research conducted has found that capital expenditure does not have a significant effect on the performance of regional governance (Artha, Basuki, & Alamsyah, 2015) and capital expenditure has a significant effect on local government performance in realizing the public welfare (Mangkunegara, 2015;Sari & Supadmi, 2016;Antari & Sedana, 2018;Astiti & Mimba, 2016;Ayinde et al, 2015 andMarfiana &Kurniasih, 2013). Thus, capital expenditure should have an impact on the financial performance of local governments in improving the welfare of the community.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Salah satu indikasi keberhasilan penyelenggaraan pemerintah daerah adalah banyaknya infrastruktur yang dibangun yang dapat tercermin dari besarnya belanja modal dalam APBD (Artha et al, 2015). Pemerintah daerah akan berupaya untuk meningkatkan anggaran belanja modalnya dengan tujuan untuk memberikan pelayanan yang terbaik kepada masyarakat.…”
Section: Gambar 1 Ekppd Terhadap Lppd Provinsi DI Indonesia Tahun 20unclassified
“…Mangkunegara (2015) used one of the elements of the financial statements, namely capital expenditure presented at the LRA, to predict its effect on the financial performance of regional governments in improving the welfare of the community. Research conducted has found that capital expenditure does not have a significant effect on the performance of regional governance (Artha, Basuki, & Alamsyah, 2015) and capital expenditure has a significant effect on local government performance in realizing the public welfare (Mangkunegara, 2015Sari & Supadmi, 2016Antari & Sedana, 2018;Astiti & Mimba, 2016;and Ayinde et al, 2015). Thus, capital expenditure should have an impact on the financial performance of local governments in improving the welfare of the community.…”
Section: Introductionmentioning
confidence: 99%